Mechanisms underlying the healing potentials of the methanol extract of Chasmanthera dependens stem on indomethacin-induced gastric ulcer. Issue 1 (1st January 2021) - Tijani, Abiola Stephanie; Farombi, Ebenezer Olatunde; Olaleye, Samuel Babafemi
ABSTRACT: Chasmanthera dependens stem is used in African traditional medicine as a remedy for various maladies; however, scientific evidence to validate its uses in gastric ulcer healing is lacking. This study investigated the mechanisms underlying the healing potentials of the methanol extract of C. dependens stem (MECD) on the indomethacin-induced gastric ulcer. Forty male Wistar rats at 8 weeks old were used in this study and divided into five groups ( n = 8). Group 1: control group, group 2: indomethacin alone (ulcerated untreated), group 3: ulcerated + 200 mg/kg MECD, group 4: ulcerated + 400 mg/kg MECD and group 5: ulcerated + 50 mg/kg cimetidine. Treatment with either MECD or cimetidine was once daily for 14 days after ulcer induction. Histological gastric injuries, antioxidant, inflammatory and apoptotic markers were evaluated. The results obtained revealed gastric mucosa damage as evident by marked histologic changes, increased ulcer score, ulcer index, lipid peroxidation, Tumor necrosis-alpha (TNF-α), Interleukin-1β (IL-1β), Cytochrome c (Cyt-c), Caspase-9 (Casp-9), Caspase-3 (Casp-3) and a number of apoptotic nuclei and significant decreased gastric antioxidant status, prostaglandin-E2 (PGE2 ) and vascular endothelia growth factor (VEGF) levels at p<  0.01. But MECD or cimetidine treatments significantly heal the ulcer and remarkably improved the biochemical parameters.